Analisa Tingkat Kebisingan Taman Bermain Anak di Timezone Mall - Nya Daniaty Malau; Angela Delviani Jehadun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Noise is one of the waveforms that can be heard by human hearing. Truth is the activation of sound that can not be done. The effect of sound on humans not only affects the auditory organ, but also can affect other organs, such as narrowing of blood vessels and heart system. Truth caused by transportation is very disturbing but not all of it is caused by transportation. Wisdom can also occur in public places or facilities such as hospitals and children's playgrounds, one of the children's and children's favorite theme parks is TimeZone Mall. You can do research to measure and learn the level of playground at TimeZone Mall Taman Anggrek and TimeZone Tamini Square. The average measured result of 6 readings with calculations per 60 minutes in the orchid mall's time zone is 70.5 dB and the tamini square time zone is 65.33 dB. In the time zone of the orchid mall park and the tamini square time zone there is no value beyond the threshold limit (85 dBA). With no measurement results exceeding the workspace limits for uninterrupted or preventive work. Keywords: Noise, Timezone Mall, playground, sound